Masswe Colonic Haemorrhage from a Solitary Caecal Varix. Issue 4 (1996) - Shaper, K. R. L.; Jarmulowicz, M.; Dick, R.; Cuthbert, N. D.; Davidson, B. R.
Abstract : A 51 year old lady with chronic active hepatitis presented with massive lower gastrointestinal tract bleeding. Angiography demonstrated a solitary varix in the caecum which was found at laparotomy to be entering the bowel wall at the site ofadhesions from a previous appendicectomy. The portal pressure was found to be raised. Aright hemicolectomy stopped the blood loss, but she subsequently died ofliver failure. Solitary colonic varices associated with adhesions are extremely rare and their optimal management has not been established.